Branch-Specific Plasticity of a Bifunctional Dopamine Circuit Encodes Protein Hunger - Liu, Qili (Science, 2017)
Free-living animals must not only regulate the amount of food they consume, but also choose which types of food to ingest. The shifting of food preference driven by nutrient-specific hunger can be essential for survival, yet little is known about the underlying mechanisms. We identified a dopamine circuit that encodes protein-specific hunger in Drosophila. The activity of these neurons is increased following substantial protein deprivation. Activation of this circuit simultaneously promoted protein intake and restricted sugar consumption, via signaling to distinct downstream neurons. Protein starvation triggered branch-specific plastic changes in these dopaminergic neurons, thus enabling sustained protein consumption. These studies reveal a crucial circuit mechanism by which animals adjust their dietary strategy to maintain protein homeostasis.